2008
DOI: 10.1088/0957-4484/19/47/475706
|View full text |Cite
|
Sign up to set email alerts
|

Maghemite–silica nanocomposites: sol–gel processing enhancement of the magneto-optical response

Abstract: The preparation and processing of maghemite-silica gel nanocomposites have been investigated in order to maximize their magneto-optical response for magnetic field sensing applications. In situ precipitation of maghemite nanoparticles from an iron salt precursor during the sol-gel processing of the silica matrix has been carried out while controlling the time, temperature, and environment at each step of the whole process. In this paper, the nanostructural, magnetic, and magneto-optical properties of these mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Diverse routes for synthesizing g-Fe 2 O 3 NPs are reported: solgel synthesis [4], electron beam deposition [5], mechanochemical synthesis [6] and pyrolysis [7], among others. However, the conventional method to obtain g-Fe 2 O 3 NPs is the oxidation of magnetite [8,9] in where particles size exceeds 12 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse routes for synthesizing g-Fe 2 O 3 NPs are reported: solgel synthesis [4], electron beam deposition [5], mechanochemical synthesis [6] and pyrolysis [7], among others. However, the conventional method to obtain g-Fe 2 O 3 NPs is the oxidation of magnetite [8,9] in where particles size exceeds 12 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Complex magnetic properties of nanosized iron oxides have been widely discussed and a wide range of magnetic properties has been obtained [1,[56][57][58][59][60][61][62]. Dutta et al reported nearly defect-free maghemite nanocrystals of a size of about 7 nm, high saturation magnetization M S = 80 emu/g close to bulk value, whereas at the same time, very low coercivity H C = 20 Oe was obtained [63].…”
Section: Introductionmentioning
confidence: 99%
“…Among them the sol-gel method has been shown to be very useful for preparation of iron oxide nanoparticles dispersed in an amorphous silica matrix. Silica is convenient because of its nontoxic nature, high biocompatibility, prevention of agglomeration, temperature resistance, chemical inertness and adjustable pore diameter [1,2,8,10,21,32,36,37,49,50,[52][53][54]57,61,67,[81][82][83][84].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has already been extensively used as a magnetic recording material for a long time [3]. Besides, it is also widely used in drug delivery, catalysis, magneto-optical device, ferro-fluids, and magnetic refrigeration [4][5][6][7][8]. Although MNPs have already been studied for many years, research on their potential use in stealth aircrafts as electromagnetic and microwave absorbing material is now the hot topic in military application [9,10].…”
Section: Introductionmentioning
confidence: 99%